2012
DOI: 10.1093/ejcts/ezr292
|View full text |Cite
|
Sign up to set email alerts
|

Durability of aortic valve preservation with root reconstruction for acute type A aortic dissection

Abstract: Aortic valve preservation and root reconstruction appear to be an appropriate surgical approach to AAAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 16 publications
1
11
2
Order By: Relevance
“…In our series, dissection involved the aortic root in 16 (14.8%) patients and the aortic arch in 9 (8.3%); however, replacement of the aortic arch and root was not associated with increased morbidity and mortality. Although these results are in agreement with the current literature, [10][11][12] we cannot make a statement in this regard due to our small sample size. Some other studies have reported higher morbidity and mortality for arch replacement compared to ascending replacement only.…”
Section: Discussionsupporting
confidence: 84%
“…In our series, dissection involved the aortic root in 16 (14.8%) patients and the aortic arch in 9 (8.3%); however, replacement of the aortic arch and root was not associated with increased morbidity and mortality. Although these results are in agreement with the current literature, [10][11][12] we cannot make a statement in this regard due to our small sample size. Some other studies have reported higher morbidity and mortality for arch replacement compared to ascending replacement only.…”
Section: Discussionsupporting
confidence: 84%
“…Gelatin‐resorcin‐formaldehyde glue (GRF) has been successfully used in aortic dissection surgery for decades . However, due to its tissue toxicity (probably due to the formaldehyde) and several series showing increased rates of the long‐term complications mentioned above, its use in these procedures has raised concerns. Albumin‐resorcin glue is believed to be less tissue toxic; however, it hardens quickly and becomes very rigid which makes dosing, uniform placement and the placement of stiches sometimes difficult; long‐term complications have been reported as well .…”
Section: Discussionmentioning
confidence: 99%
“…concluded that preservation of the aortic valve is associated to an increased risk of recurrent AR in patients presenting with moderate-to-severe AR;[18] Yamanaka et al . showed that high-grade preoperative AR improved during the postoperative follow-up after valve preservation with root reconstruction;[7] on the contrary, Bekkers et al . demonstrated that the aortic valve preservation in patients with severe preoperative AR was associated with an increased risk of aortic valve re-operation.…”
Section: Discussionmentioning
confidence: 99%
“…[67] AAD is often associated with a variable degree of concomitant aortic valve regurgitation (AR); emergency surgery has to also address the aortic valve function. [89] The choice between either conservative approach or replacement of the aortic valve is crucial and basically relies on the degree of aortic root involvement, aortic valve morphology, and the underlying mechanism of AR.…”
Section: Introductionmentioning
confidence: 99%